Analisis Pertumbuhan dan Kandungan Total Flavonoid Kultur Kalus Krisan (Chrysanthemum morifolium Ramat) dengan Pemberian Asam 2,4-diklorofenoksiasetat (2,4-d) dan Air Kelapa - Tia Setiawati; Anggita Levi Astuti; Mohamad Nurzaman; Nining Ratningsih (Pro-Life, 2021)
Chrysanthemum morifolium contains flavonoids which have antioxidant properties and was useful in treating various diseases. The production of flavonoids from plants can be done in vitro through callus culture. Auxin 2,4-D growth regulators and organic compounds such as coconut water added to the media can affect the success of callus formation and secondary metabolite synthesis. The purpose of this study was to obtain the best treatment of 2,4-D concentration and coconut water that can increase the growth and total flavonoid levels of C. morifolium callus cultures. The method used in this research was the experimental method completely randomized design (CRD) with 8 treatments, namely 1 ppm 2,4-D + 10% coconut water (CW); 2 ppm 2,4-D + 10% CW; 3 ppm 2,4-D + 10% CW ; 4 ppm 2,4-D + 10% CW; 1 ppm 2,4-D; 2 ppm 2,4-D; 3 ppm 2,4-D; 4 ppm 2,4-D in 4 replication. The results showed that the treatment of 4 ppm 2,4-D and 10% CW was the best treatment combination, resulting in an average callus size (1.4 cm), fresh weight (0.19 grams), dry weight (0.16 gram) and total flavonoid content (1.873 mgQE/g)